Efficacy of Vitis vinifera wood activated carbon in the treatment of domestic wastewater in Cachiche, Ica - Ocaña Castillo, Carlos Jefferson (2023)
The purpose of the study was to evaluate the effectiveness of activated carbon (AC) from Vitis vinifera firewood in the treatment of domestic wastewater from Cachiche, Ica, evaluating the contact time and the regeneration of AC in the removal percentage and the capacity of adsorption of COD, BOD, total coliforms, thermotolerant coliforms and E. Coli; for this, the factorial experimental design was applied. At 90 minutes of contact time and AC without regeneration revealed higher removal percentages and adsorption capacity of BOD5: 39.77 %, 9.86 mg/g; total coliforms: 58.50 %, 5.13×107 NMP/g; thermotolerant coliforms: 45.5 %, 2.00×107 MPN/g and E. coli: 71.5 %, 9.84×106 MPN/g; while the highest values for COD were 37.86 % and 17.5 mg/g, obtained with CA regenerated once and at 90 minutes. The effect of contact time was significant (p < 0,05) in the adsorption capacity of total coliforms, but for the rest of the parameters it was not significant; on the other hand, the regeneration of the AC had a significant effect on the adsorption capacity of BOD5, COD, thermotolerant coliforms, total coliforms, and E. Coli. In conclusion, AC from Vitis vinifera firewood is an effective and promising adsorbent to improve water quality.